PLC-Based Wheelchair Control with Integration of the Internet of Things - Gulpanich, Suphan; Petchhan, Jirayu; Wongvanich, Napasool (My University, 2018)
This paper presents a PLC-based mobile mecanum-wheeled wheelchair control algorithm with the integration of the Internet of Things (IoT). The design aims to enhance comfort to the handicapped by offering wireless wheelchair control in addition to the Human Machine Interface (HMI) over the Ethernet port. The bottom-up approach was taken where proportional mobility control in the vector form of speed and direction is firstly configured and displayed over the touch screen. Remote access is then designed to access through the use of the HMI Remote Viewer application which supports and displays the corresponding speed and direction on a smartphone, upon wireless communication. Results show that the communication speed is within the rapidity range, whereas the locomotion test shows an average of 8.5% drop in speed from the no-load case to the loaded case. The proposed design thus provides a complete range of wheelchair control which can be used to assist the handicapped.
Keywords: HMI; HMI Remote Viewer; Internet of Things; Mobile Mecanum Wheelchair; PLC; Smartphone